Green chemistry and coronavirus - Ahmadi, Sepideh; Rabiee, Navid; Fatahi, Yousef; Hooshmand, Seyyed Emad; Bagherzadeh, Mojtaba; Rabiee, Mohammad; Jajarmi, Vahid; Dinarvand, Rassoul; Habibzadeh, Sajjad; Saeb, Mohammad Reza; Varma, Rajender S; Shokouhimehr, Mohammadreza; et al. (Sustainable chemistry and pharmacy, 2021)
The novel coronavirus pandemic has rapidly spread around the world since December 2019. Various techniques have been applied in identification of SARS-CoV-2 or COVID-19 infection including computed tomography imaging, whole genome sequencing, and molecular methods such as reverse transcription polymerase chain reaction (RT-PCR). This review article discusses the diagnostic methods currently being deployed for the SARS-CoV-2 identification including optical biosensors and point-of-care diagnostics that are on the horizon. These innovative technologies may provide a more accurate, sensitive and rapid diagnosis of SARS-CoV-2 to manage the present novel coronavirus outbreak, and could be beneficial in preventing any future epidemics. Furthermore, the use of green synthesized nanomaterials in the optical biosensor devices could leads to sustainable and environmentally-friendly approaches for addressing this crisis.
Keywords: Optical biosensor; COVID-19; SARS-CoV-2; Early diagnosis; Point-of-care